Systemic lupus erythematosus is associated with an increased risk of cervical artery dissection - Robert J. Trager; Benjamin P. Lynn; Anthony N. Baumann; Eric Chun-Pu Chu (Scientific Reports)
Abstract Limited evidence suggests that autoimmune diseases are associated with an increased risk of cervical artery dissection (CeAD). We hypothesized individuals with systemic lupus erythematosus (SLE) would have an increased risk of CeAD following SLE diagnosis compared to matched non-lupus controls. We queried a de-identified United States electronic medical records network (TriNetX, Inc.) for individuals aged 10 and older from 2012 to 2020, for two cohorts: (1) SLE and (2) non-lupus controls, excluding those with prior CeAD. We used propensity matching to control for confounding variables and calculated the risk ratio (RR) for CeAD occurring over four years’ follow-up, secondarily exploring cumulative incidence. After matching, both cohorts contained 77,008 patients, who were mostly female (89%). The incidence and risk of CeAD was significantly greater among those with SLE compared to matched non-lupus controls [95% CI] (0.08% vs. 0.04%; RR = 2.33 [1.49;3.66]; P < 0.0001). These findings support the hypothesis that SLE is a risk factor for CeAD. Additional research is needed to identify the mechanisms that may underly the SLE-CeAD association and examine the potential association between other autoimmune diseases and CeAD.